Rim esponja medular, litiase, hipercalciuria e hiperuricosuria em crianca. Relato de um caso e evolucao - Macedo, Célia Sperandeo [UNESP]; Riyuzo, Márcia Camegaçava [UNESP]; Bastos, H. D. [UNESP]; Morcelli, J. [UNESP] (Fundacao Sociedade Brasileira de Pediatria, 1996)
The medullary sponge kidney is rare in children and may present it self with hematuria and nephrolithiasis. We report a case of medullary sponge kidney in a child with nephrolithiasis, hypercalciuria, hyperuricosuria and prolonged treatment which avoided the recurrence of nephrolithiasis.
Medullary sponge kidney, nephrolithiasis, hypercalciuria and hyperuricosuria in a child. Report of a case and follow-up
Keywords: hypercalciuria; hyperuricosuria; medullary sponge kidney; nephrolithiasis; allopurinol; citrate potassium; hydrochlorothiazide; case report; child; follow up; human; symptomatology